The Influence of Reading Culture and Learning Interest on Students' Short Story Writing Skills - Jaya, Ahmad Chandra; Purwanta, Edi; Rukiyati, Rukiyati; Sholihin, Nur; Zahra, Putri Luthfiyah; Wibisono, Dhika Dzulkarnain (Yayasan Keluarga Guru Mandiri, 2026)
The background of this study is based on reading culture and interest in learning as two important factors that influence the ability to write short stories. In this context, culture is understood as a collective habit formed through social and learning processes, which reflects individual values and attitudes towards reading activities as part of everyday life. This study used a quantitative design with an ex post facto method and involved a sample of 70 students. Data were collected using a questionnaire to measure reading culture and interest in learning, as well as a short story writing task to assess writing skills. The results showed that both variables, namely reading culture and learning interest, had a significant influence on short story writing ability, with learning interest making a slightly larger contribution. Multiple linear regression tests revealed that both contributed significantly to improvements in short story writing ability, with an R² of 0.874. The contribution of this study is to deepen the understanding of the importance of reading culture and interest in learning in improving writing skills, and to offer recommendations for developing effective teaching methods.